Tradisi Ekonomi Pasca Rosulullah Muhammad - Rini Antika, Lulu; Aulia Fitriani, Putri (INAIFAS Press, 2021)
In the history of Islamic economic civilization, some important moments can be used as literature such as the problematics of Islamic economics in the Khulafaurrasyiddin era, like the Umayyad and Abbasid dynasties. Khulafaurrasyiddin means someone who replaces or continues the struggle of the Prophet Muhammad SAW. In that era, there were many conflicts and problems that the caliphs had to face. In Abu Bakr’s period, there was a conflict about negligence in paying zakat, the rise of fake prophets, and Murtaddin. At the end of Umar ibn Khattab’s period, there was a conflict about the policy's implementation that was considered damaging to the Muslim community at that time. In the period of Utsman ibn Affan came up problems because of the corruption that were done by the official government, meanwhile, in Ali ibn Abi Talib’s period, there were many rebels (Khawarij). It also happened in the Umayyad and Abbasid dynasties, each government had its policies and conflicts as well, depending on the circumstances and people’s economy at that time. Keywords: Economic, Khulafaurrrasyiddin, Policy, Umayyad Dynasty, Abbasid Dynasty.